Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

We have a sum $\sum_{0}^{\infty} 2^{n+1}(x+1)^{3n+1}$ I am asked to find all values of x s.t this sum converges then compute the sum.

I have no idea what im doing so i did this. $\frac {2^{n}(x+1)^{3n}} {2^{n+1}(x+1)^{3n+1}}$

this yields $\frac {1}{2(x+1)^{3}}$ this looks alittle wierd but i just move it over and solved to get $x=-1 +2^{-1/3}$ this isnt right i also have no idea to find the sum if it was please help.

share|cite|improve this question
up vote 2 down vote accepted

First you should realize that just about the only series you've learned how to get an explicit sum for is a geometric series. So your first goal should be to make the given series looks like the standard form of a geometric series. One way to do this is as follows: \begin{align} \sum_{n = 0}^\infty 2^{n+1} (x+1)^{3n+1} & = 2(x+1) \sum_{n = 0}^\infty 2^{n} (x+1)^{3n} \\ & = 2(x+1) \sum_{n = 0}^\infty (2(x+1)^3)^n. \end{align} Now $\displaystyle \sum_{n = 0}^\infty (2(x+1)^3)^n$ is a geometric series with $a = 1$ and $r = 2(x+1)^3$. Hence $$\sum_{n = 0}^\infty (2(x+1)^3)^n = \frac{1}{1 - 2(x+1)^3},$$ and from the work about it follows that $$\sum_{n = 0}^\infty 2^{n+1} (x+1)^{3n+1} = 2(x+1) \sum_{n = 0}^\infty (2(x+1)^3)^n = \frac{2(x + 1)}{1 - 2(x+1)^3}.$$

A geometric series $\displaystyle \sum_{n=0}^\infty ar^n$ converges if and only if $|r| < 1$, so our given series converges if and only if $$|2(x+1)^3| < 1 \iff -1 - 2^{-1/3} < x < -1 + 2^{-1/3}.$$

share|cite|improve this answer
that is really obvious i just couldn't understand what to make a O.o thank you. – Faust7 May 10 '13 at 22:35

Recall the geometric series $$a+ar+ar^2+ar^3+\cdots+ar^n+\cdots \tag{$\star$}$$ converges for $\vert r \vert < 1$ and equals $\dfrac{a}{1-r}$.

Try to write your series in the above form $(\star)$, for a suitable $a$ and $r$.


$$\sum_{n=0}^{\infty} 2^{n+1} (x+1)^{3n+1} = 2(x+1) \sum_{n=0}^{\infty}\left(2(x+1)^3\right)^n$$ Can you now see it?

share|cite|improve this answer
well tis nothing like that form but r or is 2(x+1) the other is $2(x+1)^{3}$ – Faust7 May 10 '13 at 22:30
@Faust7 I added some more to the answer. Can you now see it? – user17762 May 10 '13 at 22:32
not really i wrote that down on my paper before i tried the gibberish above that exact line and had no idea what to do with it so i tried something else. – Faust7 May 10 '13 at 22:33

Your original sum is:


We can rearrange the summation as

$$\sum_{n=0}^\infty{2 \cdot (2^n)(x+1)^{3n}(x+1)}$$ $$=\sum_{n=0}^\infty{2\left(2(x+1)^3\right)^n(x+1)}$$ $$=\sum_{n=0}^\infty{\left(2(x+1)^3\right)^n2(x+1)}$$

So we are interested in what happens when $n$ approaches infinity. In order for this sum to converge we need $2(x+1)^3$ to get smaller and smaller. Do you know what to do next?

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.